A new and little known species of Protoribates (Acari: Oribatida: Haplozetidae) from Babeldaob Island of Palau. Issue 4 (18th May 2020) - Bayartogtokh, Badamdorj; Shimano, Satoshi
ABSTRACT: We found four species of oribatid mites belonging to the genus Protoribates from Babeldaob Island of Palau Republic, which is an island country located in the western Pacific Ocean. A new species, Protoribates lutosisetosus sp. nov . is described from litter and soil of the primary and secondary forests in Palau, and supplementary descriptions of three hitherto known species, Protoribates acutus, Protoribates paracapucinus, and Protoribates seminudus are provided. Following the descriptions and comparisons, aspects of the taxonomy, distribution, and habitat ecology of all studied species are discussed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:5D27105E-EA22-4909-8A16-16836F8FF41D